Implementasi Metode AHP dan Topsis Pemilihan Smartphone iOS Gaming Terbaik - Aggiano Wahyu Pratama; Zuly Budiarso (LPPM UBHINUS MALANG, 2024)
In the current era, cell phones are an important component in everyday life. Rapid advances in smartphone technology are opening up new opportunities in various aspects of life, including in the world of gaming. Users are often confused when choosing an iOS model that meets the criteria for their gaming needs. In solving this problem, a system is needed to serve consumers to choose the top iOS smartphone for gaming needs based on predetermined criteria. Price, graphics capabilities, storage capacity, RAM, OS version, and battery life of the six available iPhone models are the criteria used in this research. The system implements the AHP (Analytical Hierarchy Process) method to get the criteria weighting numbers and TOPSIS (Technique for Others Preference by Similarity to Ideal Solution) to get the priority order of the highest to lowest numbers. From the calculations, the highest values ​​obtained are iPhone 12 Pro Max (1), iPhone 12 Pro (0.528), iPhone 11 Pro (0.448), iPhone 12 (0.301), iPhone 11 Pro Max (0.222), and the lowest value is iPhone 11 ( 0.204). Based on these findings, consumers can make an informed decision regarding which iPhone is best for gaming. This system will make it easier for users to determine the best iOS smartphone for playing games.